Uma aplicação de redes definidas por software para a gerência de redes de datacenters virtualizados - Rogerio Vinhal Nunes (2012)
Cloud-Computing services related to infrastructure have been drawing much attention recently. On this business model, virtualization is an efficient way to ofier flexibility, isolation and several new functionalities. This technology has led to the multi-tenant datacenter model for Cloud-Computing, where the client (tenant) can rent not only avirtual machine, but a network of virtual machines in the provider infrastructure. Despite of the recent virtualization products already offering isolation solutions for resources such as CPU and memory, this new business model require network isolation solutions for each tenant that, as of today, are offered in limited, expensive and unscalable ways like the use of VLANs. Parallely, the academic community have recently focused on the development of Software-Defined Networks (SDNs) due to thedefinition of the OpenFlow standard. This new approach allows the network to be organized in a more flexible way, with a global centralized vision of the network. This project presents DCPortals, which implements a virtual network view for each client of a multi-tenant Cloud-Computing service without the need to use specialized hardware. It is implemented using the POX Network Operating System along with the OpenStack Cloud-Computing manager controlling machines with the Xen VirtualMachine Monitor. These machines are connected by Open vSwitch virtual switches that are capable of using the OpenFlow protocol. Therefore, each client can not only rent virtual machines, but also connect them in a private virtual network isolated from every other machine independently of how the machines are organized in the underlying physical infrastructure.The experiments confirmed the network isolation even in attack cases and showed that the observed overhead is limited to the first packet of a flow between virtual machines.Keywords: Datacenter, Cloud-Computing, Virtualization, Software-Defined Networks.